Maternal mental healthcare needs of refugee women in a State Registration and Reception Centre in Germany: A descriptive study - Kaufmann, Claudia; Zehetmair, Catharina; Jahn, Rosa; Marungu, Rosi; Cranz, Anna; Kindermann, David; Friederich, Hans-Christoph; Bozorgmehr, Kayvan; Nikendei, Christoph (Health and social care in the community, 2022)
Pregnant refugees and new mothers are at high risk of developing mental health problems. Previous research has highlighted an increase in adverse pre-, peri- and postpartum outcomes in refugee women and their newborns. This descriptive study aimed to present the characteristics and needs of refugee women who attended a psychosocial walk-in clinic addressing pregnant refugees’ and new mothers’ maternity mental healthcare needs in a state registration and reception centre in Germany. We assessed all patients that consulted the clinic and received interventions during the first 28 weeks after it opened, collecting information on symptoms, diagnoses, attitudes towards and experience of pregnancy, birth, obstetric care and applied psychosocial interventions during consultations. Between November 2017 and May 2018, N = 120 pregnant refugees and new mothers attended the clinic. Most patients were diagnosed with post-traumatic stress-, adjustment- or depressive disorder. While 69.6% of the women reported physical and mental health problems during pregnancy, 87.4% experienced obstetric complications. Trauma-informed and psychoeducational interventions were primarily used during counselling sessions. Our data underpin the glaring disparities in refugee maternal healthcare in Germany. Maternal care designed to meet the specific needs of pregnant refugees and mothers is essential. More targeted, evidence-based and cost-effective interventions are needed. Our psychosocial walk-in clinic is a first step towards ensuring primary care delivery for refugee women during the particularly vulnerable period of pregnancy and early motherhood.